2008
DOI: 10.1002/aoc.1458
|View full text |Cite
|
Sign up to set email alerts
|

AACVD of WO3 thin films from W(O)(OPri)3[O(CH2)nNMe2] (n = 2, 3)

Abstract: Monomeric tungsten oxo-aminoalkoxides W(O)(OPr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Oxygen-bound ligands such as oxo, alkoxide, β-diketonate and β-ketoesterate moieties have found use in single source precursors for the deposition of metal oxides because the preexisting metal oxygen bonding can facilitate conversion of the precursor to the oxide material during deposition [25,[34][35][36]. We have previously demonstrated that oxo alkoxide complexes of the type WO(OR) 4 (R = C(CH 3 ) 2 CF 3 and C(CF 3 ) 2 CH 3 ) and the dioxo derivative WO 2 (OR) 2 L (R = C(CF 3 ) 2 CH 3 , L = DME) are low temperature precursors to WO x films and nanorods, consistent with incorporation of the terminal oxo moieties into the deposits [23,41,42].…”
Section: Precursor Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen-bound ligands such as oxo, alkoxide, β-diketonate and β-ketoesterate moieties have found use in single source precursors for the deposition of metal oxides because the preexisting metal oxygen bonding can facilitate conversion of the precursor to the oxide material during deposition [25,[34][35][36]. We have previously demonstrated that oxo alkoxide complexes of the type WO(OR) 4 (R = C(CH 3 ) 2 CF 3 and C(CF 3 ) 2 CH 3 ) and the dioxo derivative WO 2 (OR) 2 L (R = C(CF 3 ) 2 CH 3 , L = DME) are low temperature precursors to WO x films and nanorods, consistent with incorporation of the terminal oxo moieties into the deposits [23,41,42].…”
Section: Precursor Designmentioning
confidence: 99%
“…Single source precursors for deposition of WO x include tungsten alkoxide complexes [25,27,[34][35][36][37]. However, these complexes are air-and water-sensitive, which complicates their practical use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such films are usually produced either by hydrolysis of a suitable precursor in a sol-gel protocol, [7] or by chemical vapour deposition (CVD) from a volatile precursor. [8][9][10] The properties of these films can be modified by the inclusion of a variety of additional metals, [11][12][13] which from a technological perspective require co-hydrolysis of two metal moieties (sol-gel) or a dual-source CVD approach. One variation which removes the practical difficulties of matching hydrolysis / decomposition rates is the use of a single-source precursor (SSP) which incorporates both metals in the same molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Hbdmap 8 was prepared by literature method; [W(O)(O i Pr) 4 ] 2 and W(O)(OPr i ) 3 (dmae) (1) were prepared as described elsewhere. 9 Synthesis of W(O)(OPr i ) 3 (bdmap) (2). [W(O)(O i Pr) 4 ] 2 (3.00 g, 6.87 mmol) was dissolved in toluene (ca.…”
Section: Experimental Section General Proceduresmentioning
confidence: 99%